6. THE EVALUATION OF THE THERAPEUTIC EFFECT OF NON-ALCOHOLIC FATTY LIVER DISEASE OF THE COMBINATION DECOCTION OF CHAIHU SHUGAN TANG AND ERCHEN TANG (Vietnam Journal of Community Medicine, 2023)
Background: Fatty liver disease is characterized by abnormal accumulation of fat in liver cells due to various causes. Modern medicine currently lacks a specific treatment method, mainly focusing on improving diet and exercise. Therefore, researching traditional herbal medicine to support the treatment of fatty liver disease is a new direction. Objectives: To evaluate the therapeutic effects and monitor any potential adverse effects of the combination of Chaihu Shugan tang and ErChen tang on NAFLD treatment. Subjects and methods: A clinical intervention study was conducted on 35 NAFLD patients using the herbal combination of Chaihu Shugan tang and ErChen tang. Clinical and subclinical outcomes were evaluated through liver ultrasound and various blood biochemical indices, including cholesterol, triglycerides, HDL-C, LDL-C, AST, ALT, and GGT. The study lasted 84 days, from June 2022 to December 2022, at Da Nang Traditional Medicine Hospital. Results: After the intervention, both clinical and subclinical symptoms were significantly improved. The levels of cholesterol, triglyceride, HDL-C, and LDL-C improved by 28.39%, 30.13%, 11.30%, and 37.08%, respectively. Additionally, there was an 11.28% improvement in AST levels, a 21.53% improvement in ALT levels, and a 21.11% improvement in GGT levels. Statistical significance at p < 0.05. Conclusion: The herbal combination of Chaihu Shugan tang and ErChen tang effectively improved the clinical symptoms of non-alcoholic fatty liver disease. Subclinically, the combination improved cholesterol, triglycerides, HDL-C, LDL-C, AST, ALT, GGT, and reduced liver fat accumulation on ultrasonography without showing any adverse effects during the study period.
Keywords: Chaihu Shugan tang, Er Chen tang, Non-alcoholic fatty liver disease.